(untitled) (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
The transition to Industry 4.0 has widened the gap between the competencies of high school graduates and the job market demands for innovation, value creation, and independence. This study aims to examine the effectiveness of the School Plantation-Based Entrepreneurship Program at SMA Negeri 1 Payaraman, South Sumatra, which utilizes local agricultural resources. The program aims to improve entrepreneurial competency, life skills and independence, as well as attitude transformation—particularly entrepreneurial motivation and self-efficacy—through experiential learning across the agribusiness value chain. The research method used a qualitative-evaluative case study design guided by the CIPP (Context, Input, Process, Product) framework. Data were collected from 30 students, school leaders, and mentor teachers through in-depth interviews, participant observation, and document analysis, complemented by quasi-quantitative assessments to determine success rates. Results indicate the program is highly effective, achieving an average success rate of 83.3%. Students’ entrepreneurial competency increased significantly (85% mastery of business planning and product processing), while life skills and independence reached 75%. The most notable improvements occurred in attitude changes and self-efficacy, which increased by 90%. External impacts include a 25% increase in partner income and 90% increase in partner satisfaction. The study concluded that a local resource- and experience-based entrepreneurship model can bridge the competency gap by strengthening technical skills, digital marketing, decision-making autonomy, and an entrepreneurial mindset. The novelty of this research lies in the integration of school farms as living agribusiness laboratories within the CIPP-evaluated empowerment framework, offering a sustainable and replicable model of entrepreneurship education in similar socio-economic settings.